LEXICAL ERROR IN WRITING ENGLISH WORDS MADE BY STUDENTS OF THE JUNIOR HIGH SCHOOL - Bahrun Amin (Universitas Muhammadiyah Makassar, 2014)
The objectives of the research are to find out: The lexical error in writing English noun made by the eighth-grade students of SMP Unismuh Makassar. The lexical error in writing English adjective made by the eighth-grade students of SMP Unismuh Makassar. What lexical error in writing English verb is made by the eighth-grade students of SMP Unismuh Makassar. The result of this research gives information caused by the lexical error of the student’s ability in writing English noun and adjective especially. For the teacher: the result of this research can be a knowledge and references to all teacher why their students have low ability in writing vocabulary, and also find out the solution so that can create students whose more quality. For students: make students realize their mistake in learning vocabulary, and they can repair their mistake by changes their way in study vocabulary. For researcher: it can be known and references for researcher about the cause of lexical error in writing English words, it also becomes a description of some problem that faces in the school especially to students. Moreover, it can make research have more knowledge how to be a good teacher in the next future.Keyword: Lexical, writing, Junior high school, vocabulary, error